Transit Systems and Ridership under Extreme Weather and Climate Change Stress: An Urban Transportation Agenda for Hazards Geography. Issue 11 (November 2015) - Barnes, Mark
Abstract: This review examines studies that detail the effects of weather and climate on urban transit systems and ridership. The aim is to help revitalize a hazards geography research agenda to support stakeholder decision‐making on hazard risk and disaster vulnerability for US transit systems and ridership. Largely representative of the literature are field perspectives outside of hazards geography whose predispositions to positivism neglect equity concerns of vital importance to hazard risk mitigation, vulnerability reduction, adaptation, and resilience research and practitioner communities. The article argues for hazards geography's perspectival insight to fill this void. Themes discussed in the article include hazards geography value, transit system vulnerability to meteorological and non‐meteorological factors, place‐based climate change vulnerability assessments, policymaker and managerial perceptions of climate change, and transit ridership choice. The article concludes with a call to hazards geographers to conduct critical assessments of structural and non‐structural adaptation measures, investigate mobility decision‐making and coping strategies, and develop theoretical understandings on adaptation policymaking and practice in relation to hazard risk and disaster vulnerability.